Supporting Pervasive and Social Communications with FRASCATI - Mélisson, Rémi; Romero, Daniel; Rouvoy, Romain; Seinturier, Lionel (Electronic Communications of the EASST, 2010)
In pervasive environments, the runtime adaptation of applications is done considering available event sources and services. To do that, the events have to be collected and processed, and the volatile services identified and accessed. However, although the event flow and service mobility are key issues in the adaptation process, existing solutions fail to deal with them in a simple and flexible way. Therefore, in this paper we propose to face these issues by combining the SCA (Service Component Architecture) standard, micro-blogging services and discovery technologies. In particular, we benefit from the SCA extensibility, supported by the binding concept, for introducing two new communication mechanisms: i) social bindings, allowing synchronous event exchange via Twitter and, ii) pervasive bindings that provide support for discovery using standard protocols such as UPnP. We add support for these bindings in FRASCATI (a platform for SCA) and illustrate their usage with a smart home scenario that requires the integration of heterogeneous technologies.